Larval descriptions of Annitella esparraguera (Schmid 1952) and Annitella iglesiasi González & Malicky 1988 (Trichoptera: Limnephilidae), two endemic species from Southern Europe - Sáinz-Bariáin, Marta; Zamora-Muñoz, Carmen (Zootaxa, 2015)
Descriptions of the previously unknown larvae of Annitella esparraguera and A. iglesiasi, two European endemic species from the southern Iberian Peninsula are presented. The most important diagnostic features are illustrated and some taxonomic, zoogeographical and ecological notes are given. In addition, a previous key is modified to include these two new Iberian Limnephilidae larvae.